EVALUASI PEMBELAJARAN ONLINE MATEMATIKA SISWA SEKOLAH DASAR - Anugraini, Asri Putri (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
Mathematics learning is currently less efficient in the pandemic season because it reduces all face-to-face activities between teachers, students and their friends. This study aims to determine the ease and constraints of online learning mathematics for grade 4 SD Negeri Kedung Pedaringan. This type of research was descriptive qualitative. Data collection in the form of interviews and questionnaires containing questions to determine effectiveness during online learning activities during the covid 19 pandemic. The results of research through interviews and questionnaires stated that online learning without face-to-face was transferred to internet access and social media in the form of WhatsApp applications and google meet applications. Some of the conveniences of online learning were learning activities did not have to be at school, time and place were free as long as learning evaluation activities were known directly by the teachers. Some of the problems of online learning were students had difficulty of understanding the material, the teacher were not optimal in explaining the material in detail, not all the parents of students understand the material given by the teachers, unstable internet access has disrupted students' online learning.